β-Xylosidase and β-mannosidase in combination improved growth performance and altered microbial profiles in weanling pigs fed a corn-soybean meal-based diet - Shaoshuai Liu; Chang Ma; Ling Liu; Dong Ning; Yajing Liu; Bing Dong (Asian-Australasian Journal of Animal Sciences, 2019)
Objective In this study, two glycosidases (XMosidases), β-xylosidase and β-mannosidase, were investigated on their in vitro hydrolysis activities of feed and on the improvement of growth performance in vivo in weanling pigs. Methods Enzyme activities of XMosidases in vitro were evaluated in test tubes and simulation of gastric and small intestinal digestion, respectively, in the presence of NSPase. In vivo study was performed in 108 weaned piglets in a 28-d treatment. Pigs were allotted to one of three dietary treatments with six replicate pens in each treatment. The three treatment groups were as follows: i) Control (basal diet); ii) CE (basal diets+CE); iii) CE-Xmosidases (basal diets+ CE+β-xylosidase at 800 U/kg and β-mannosidase at 40 U/kg). CE was complex enzymes (amylase, protease, xylanase, and mannanase). Results In vitro XMosidases displayed significant activities on hydrolysis of corn and soybean meal in the presence of non-starch polysaccharide degrading enzymes (xylanase and β-mannanase). In vitro simulation of gastric and small intestinal digestion by XMosidases showed XMosidases achieved 67.89%±0.22% of dry matter digestibility and 63.12%±0.21% of energy digestibility at 40°C for 5 hrs. In weanling pigs, additional XMosidases to CE in feed improved average daily gain, feed conversion rate (p<0.05), and apparent total tract digestibility of crude protein (p = 0.01) and dry matter (p = 0.02). XMosidases also altered the gut bacterial diversity and composition by increasing the proportion of beneficial bacteria. Conclusion Addition of a complex enzyme supplementation (contained xylanase, β-mannanase, protease and amylase), XMosidases (β-xylosidase and β-mannosidase) can further improve the growth performance and nutrient digestion of young pigs.